Media-based Youth Sexual Violence Prevention Education in Panti Village, Panti Subdistrict, Jember Regency: Edukasi Pencegahan Kekerasan Seksual Pada Remaja Berbasis Media di Desa Panti, Kecamatan Panti, Kabupaten Jember - Yeni Astuti, Soekma; Aji, Fajar; Aris Kartika, Bambang; Umniyyah, Zahratul; Dewi, Agustina; Mustika Ningrum, Rara (KHD Production, 2024)
Nowadays, society is presented with rampant cases of sexual harassment and violence. Teenagers are one of the categories of victims, so it is important to make serious prevention efforts so that the chain can be broken. Counseling activities are aimed at educating adolescents about sexual violence, how it occurs, the causes and consequences caused, how prevention efforts to reporting mechanisms for victims. Looking at the situation in the field, many teenagers do not understand the dangers of sexual violence, especially media-based violence, so this service is deemed necessary. Implementers together with partners agreed to carry out these activities with the aim of educating the community, especially teenagers who use active gadgets to avoid media-based sexual harassment and violence and know things that endanger themselves. This service broadly wants to create an environment that is safe, comfortable and free from sexual violence and is able to place Panti village as a gender-friendly village. To achieve this big goal, the main activities that will be carried out are: 1). Education on the dangers of sexual violence in general 2). Socialization of the legal umbrella of sexual violence, 3) Media-based sexual violence, and 4) Anticipation of sexual violence and protection efforts for victims.